4(3q-5)-q=-q+16

Simple and best practice solution for 4(3q-5)-q=-q+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3q-5)-q=-q+16 equation:


Simplifying
4(3q + -5) + -1q = -1q + 16

Reorder the terms:
4(-5 + 3q) + -1q = -1q + 16
(-5 * 4 + 3q * 4) + -1q = -1q + 16
(-20 + 12q) + -1q = -1q + 16

Combine like terms: 12q + -1q = 11q
-20 + 11q = -1q + 16

Reorder the terms:
-20 + 11q = 16 + -1q

Solving
-20 + 11q = 16 + -1q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add 'q' to each side of the equation.
-20 + 11q + q = 16 + -1q + q

Combine like terms: 11q + q = 12q
-20 + 12q = 16 + -1q + q

Combine like terms: -1q + q = 0
-20 + 12q = 16 + 0
-20 + 12q = 16

Add '20' to each side of the equation.
-20 + 20 + 12q = 16 + 20

Combine like terms: -20 + 20 = 0
0 + 12q = 16 + 20
12q = 16 + 20

Combine like terms: 16 + 20 = 36
12q = 36

Divide each side by '12'.
q = 3

Simplifying
q = 3

See similar equations:

| 33x^2-11x^4= | | -3a-10=2(1-a)+3a | | 4x-3=-1.72 | | 6s+6=-4 | | 4x(6-3)=94 | | -3n-9=0 | | 16m^4+9n^4=0 | | 375=4p-175 | | 8-7x=8(1+7x) | | (0.5*2.5)*x=3.5 | | 4(6-3)=94 | | -10=-9+x/4 | | 4x-3=1.72 | | r^3-11r^2+36r-36= | | 7m-6=65 | | 9-3r=2h | | -5(x-4)-3(-2-x)=x-2 | | 42+17r=-14r+-42 | | 4.2+2=10 | | 180=7x-13+2x+2+4x+9 | | 8=5-3x-6 | | X-5=2x-24 | | -25=5(w-7)-7w | | 4u^4+68u^2+280=0 | | 8=4-6b+2b | | 15=6-3n | | 72yp-12y= | | 5x+500=150 | | -9=3+5a-7 | | -4.9x^2+7.4x+10.9=0 | | 190=7x-13+2x+2+4x+9 | | 5y+13+5-3y=m |

Equations solver categories